A Dual-Port Circular Polarized S-Band Antenna for Nanosatellite Communication System. (January 2019) - Alam, Touhidul; Tariqul Islam, Mohammad; Cho, Mengu
Abstract: In recent years, the development of the nanosatellite is not for the just research purpose but commercial opportunities as well. The antenna is a very important part of the nanosatellite communication system. This paper presents an S-band circular polarized (CP) antenna for nanosatellite space mission communication system. The antenna is designed on Rogers 5880 substrate materials and the electrical dimension of the antenna is 0.39λ × 0.39λ × 0.03λ. The result shows that the antenna has a-10dB reflection coefficient bandwidth of 15.625%, 3dB axial-ratio bandwidths of 70MHz and peak gain of around 6.68dB.